An Application of Self-Organizing Map for Multirobot Multigoal Path Planning with Minmax Objective - Faigl, Jan (Computational intelligence and neuroscience, 2016)
In this paper, Self-Organizing Map (SOM) for the Multiple Traveling Salesman Problem (MTSP) with minmax objective is applied to the robotic problem of multigoal path planning in the polygonal domain. The main difficulty of such SOM deployment is determination of collision-free paths among obstacles that is required to evaluate the neuron-city distances in the winner selection phase of unsupervised learning. Moreover, a collision-free path is also needed in the adaptation phase, where neurons are adapted towards the presented input signal (city) to the network. Simple approximations of the shortest path are utilized to address this issue and solve the robotic MTSP by SOM. Suitability of the proposed approximations is verified in the context of cooperative inspection, where cities represent sensing locations that guarantee to "see" the whole robots' workspace. The inspection task formulated as the MTSP-Minmax is solved by the proposed SOM approach and compared with the combinatorial heuristic GENIUS. The results indicate that the proposed approach provides competitive results to GENIUS and support applicability of SOM for robotic multigoal path planning with a group of cooperating mobile robots. The proposed combination of approximate shortest paths with unsupervised learning opens further applications of SOM in the field of robotic planning.
Keywords: Pattern Recognition, Automated; algoritmy; Robotics; Space Perception; cestování; Motion; Humans; vnímání prostoru; pohyb těles; lidé; rozpoznávání automatizované; Neural Networks, Computer; umělá inteligence; Travel; Algorithms; Artificial Intelligence; neuronové sítě; robotika